ANSWER:
a) 63 kg
b) 0.74 m
Explanation:
Given:
F1 = 435 N
F2 = 183 N
L = 2.5 m
a)
Here the two forces F1 and F2 are actingupwards and his weight acting downwards.
![\begin{gathered} \sum ^{}_{}F_y=F_1+F_2-W=0 \\ W=F_1+F_2 \\ m\cdot g=F_1+F_2 \\ m=(F_1+F_2)/(g) \\ \text{ replacing} \\ m=(435+183)/(9.81) \\ m=62.99\cong63\text{ kg} \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/4awx667gw9ko8bgwdsuollp6vsei905k2r.png)
By using the principles of torque we get:
![\sum ^{}_{}\tau=L\cdot F_2-x\cdot W=0](https://img.qammunity.org/2023/formulas/physics/college/f0mr3ehope7ziu716ic67pijpf0gojiifx.png)
here x is the centerof the mass, solving and replacing for x:
![\begin{gathered} L\cdot F_2-x\cdot W=0 \\ L\cdot F_2=x\cdot W \\ x=(L\cdot F_2)/(W) \\ x=(L\cdot F_2)/(m\cdot g) \\ x=(2.5\cdot183)/(63\cdot9.81) \\ x=0.74\text{ m} \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/kz2hgnx6tflkme09r99kpywyhcrh4t4nbk.png)